Functional Outcome Of Monteggia Fracures Treated Primarily With Plate Fixation A Rectrospective Study Of The Outcome - Wong Teik, Pooi (2001)
Fractures of the foreann with dislocation of the radial head are known as Monteggia fractures-dislocation. This eponym is among the most widely recognized by orthopaedic surgeons, largely because of the notoriously poor results associated with the treatment of these injuries, particularly in adults. In addition to restoration of length, apposition and normal axial alignment and correct rotational alignment must also be achieved if a good range of pronation and supination is to be restored.